Evidence for interactions between the mitochondrial import apparatus and respiratory chain complexes via Tim21-like proteins in Arabidopsis - Murcha, Monika W.; Kubiszewski-Jakubiak1, Szymon; Wang, Yan; Whelan, James (Frontiers in Plant Science, 2014)
The mitochondrial import machinery and the respiratory chain complexes of the inner membrane are highly interdependent for the efficient import and assembly of nuclear encoded respiratory chain components and for the generation of a proton motive force essential for protein translocation into or across the inner membrane. In plant and non-plant systems functional, physical and evolutionary associations have been observed between proteins of the respiratory chain and protein import apparatus. Here we identify two novel Tim21-like proteins encoded by At2g40800 and At3g56430 that are imported into the mitochondrial inner membrane and found to associate with respiratory chain Complex I, III, and the TIM17:23 translocase of the inner membrane. These results are discussed further with regards to the regulation of mitochondrial activity and biogenesis.